Electronic Markets Untuk Usaha Mikro, Kecil dan Menengah Dalam Rangka Memasuki Pasar Bebas Masyarakat Ekonomi ASEAN (MEA) - Sadik, Muh. Nur (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2016)
In a global market the boundaries of the municipality/area of the world is in the era of Economic Digital is not known yet, to him it is the readiness of taking advantage of opportunities to market to the world market the product and potential - regional asset owned through electronic markets is something that is very strategic in order to advance society lasimnya as has been done by the developed countries. In the world of new trade takes place on a medium electronic where the message can be received, the image happens we can see through the computer that can connect with millions of channels in the world we commonly call cyberspace electronics, small things can eliminate the geographical distance that limits of a market to another. The main shift in a trade that has geographical distance into cyberspace represent an extraordinary change in humanitatian organizations and required an objective that can be understood and bring about chnge very quickly from any perception to the human and social relations. In order to utilize the opportunity of the free market the Asean Economic Community (AEC_ in the era of the digital economy, the Electronic Markets both traditional Electronic Data Interchange (EDI) and the new paradigm of Electronic Data Interchange (EDI) is a matter that cannot be circumvented by the municipality/regions in the world be able to acess global outlets.